(untitled) (Research, Society and Development, 2022)
Objective: To identify the teaching of care practice in oncology from the perspective of students of an Undergraduate Nursing Course at a Federal University. Materials and methods: descriptive study with a qualitative approach, with 54 students of an Undergraduate Nursing Course at a University located in the state of Rio de Janeiro, between November 2020 and January 2021, through a virtual questionnaire. Thematic-category content analysis was performed. Results: Three categories respond to the objective: teaching strategies in oncology; themes addressed in training; and proposals from students for the qualification of teaching in oncology. Teaching strategies cover compulsory and optional subjects; in addition to extracurricular activities, focused on the content of the field of primary and hospital care. Theoretical strategies, more present than the teaching-practical strategies, were related to the stages of cancer, basic concepts of oncology and nursing practice. Conclusion: Participants showed the need to include oncology in the various disciplines that make up the curriculum and use participatory methodologies. Attention is drawn to the need for further studies that identify the teaching of oncology practice in the training of nurses, in order to qualify teaching strategies and methodologies.